WESTERN ART, CULTURE AND MUSICAL INSTRUMENTS (Ustozlar uchun, 2024)
Annotation: Arabic music is the musical culture of the Arabs. Its historical roots are connected with the cultural traditions of the Bedouin tribes. The poet of the tribe performed his poems in the form of songs and musical tones. Many musical-poetry genres were formed in connection with everyday living conditions, family and religious ceremonies. This article provides information about Western musical culture, particularly the musical instruments of the Arab people